Orchid eaudiobook - Castle, Jayne (St. Helen's, 2019)
The wildly popular alter ego of bestselling author Jayne Ann Krentz creates "delectably entertaining paranormal romantic suspense" ( Booklist ) in the "unique, synergistic world of St. Helen's" ( Library Journal ), the not-so-distant space colony where hearts and minds are gloriously in sync. A top psychic for exclusive Psynergy Inc., Orchid Adams has her hands full with a baffling murder—which doesn't exactly allow time for husband hunting. Is it even possible there's a man on St. Helen's who measures up to her dreams of wedded bliss? Take her new client, Rafe Stonebraker: primitive and elemental, an unlicensed P.I. with some serious secrets, Rafe is hardly marriage material. So why does his powerful presence have Orchid imagining the most outrageous affair? Rafe is embroiled in solving a strange theft while thwarting a hostile takeover of Stonebraker Shipping; he needs a wife—and fast—to salvage his credibility. Orchid Adams doesn't fit the profile he had in mind, but she fits in his arms. Will their electrifying connection end up getting them burned?